Cohort Change Ratios and their Applications - Baker, Jack; Swanson, David A.; Tayman, Jeff; Tedrow, Lucky M. (Springer International Publishing : Imprint: Springer, 2017)
This textbook focuses on the cohort change ratio (CCR) method. It presents powerful, yet relatively simple ways to generate accurate demographic estimates and forecasts that are cost efficient and require fewer resources than other techniques. The concepts, analytical frameworks, and methodological tools presented do not require extensive knowledge of demographics, mathematics, or statistics. The demographic focus is on the characteristics of populations, especially age and sex composition, but these methods are applicable estimating and forecasting other characteristics and total population. The book contains more traditional applications such as the Hamilton-Perry method, but also includes new applications of the CCR method such as stable population theory. Real world empirical examples are provided for every application; along with excel files containing data and program code, which are accessible online. Topics covered include basic demographic measures, sources of demographic information, forecasting and estimating (both current and historical) populations, modifications to current methods, forecasting school enrollment and other characteristics, estimating life expectancy, stable population theory, decomposition of the CCR into its migration and mortality components, and the utility of the CCR. This textbook is designed to provide material for an advanced undergraduate or graduate course on demographic methods. It can also be used as a supplement for other courses including applied demography, business and economic forecasting and market research.